The role of ontogenetic allometry and nonallometric flower shape variation in species‐level adaptive diversification – Calceolaria polyrhiza (Calceolariaceae) as a case study. Issue 3 (29th December 2020) - Strelin, Marina M.; Cosacov, Andrea; Chalcoff, Vanina R.; Maubecin, Constanza C.; Sérsic, Alicia N.; Benitez‐Vieyra, Santiago M.
Abstract: Organism shape changes predictably during ontogeny, resulting in specific patterns of ontogenetic allometry. In several plant and animal lineages, among‐species variation in the shape of mature organisms mirrors variation along their growth trajectories. Hence, ontogenetic allometry is an important bias in evolution. This bias should be stronger at reduced evolutionary time scales, in which among‐trait correlations had less time to evolve. Nevertheless, it was shown that adaptation of organism shape frequently involved departures from the ancestral ontogenetic allometry. Moreover, only a moderate fraction of shape variation is correlated with size during ontogeny. Hence, nonallometric variation in shape (NAVSh) is likely to contribute to adaptation, even at reduced evolutionary time scales. We explored the contributions of allometric variation in shape (AVSh), NAVSh, and size variation to adaptive evolution in the angiosperm species Calceolaria polyrhiza . This strongly relies on oil‐collecting bees for pollination and experienced transitions in the size of pollinators during the last 2 Ma. Using geometric morphometrics, we described corolla morphology in several populations across its distribution range. Variation in corolla shape was decomposed into an allometric and a nonallometric component, and corolla size was estimated. We then looked for the correlation between these aspects of morphology and the pollinator. Our results suggest that adaptation to pollinators with different sizes relied on NAVSh, which resulted from shifts in the allometric slope and from shape changes that occurred early in flower development. We conclude that NAVSh can contribute to adaptation in flowering plants, even at the species‐level. Abstract : Research Highlights: Even at the evolutionary time scale of population divergence within a species, adaptation to different pollinators is not constrained by ontogenetic allometry.